Exploring teachers' meta-strategic knowledge of science argumentation teaching with the repertory grid technique. Issue 2 (22nd January 2017) - Lin, Yu-Ren; Hung, Cheng-Yu; Hung, Jeng-Fung
ABSTRACT: This study investigated two science teachers' meta-strategic knowledge (MSK) of argumentation teaching by applying the repertory grid technique (RGT). One teacher was a novice, while the other was experienced in teaching argumentation. Using the RGT, we elicited the objectives and strategies of the two teachers regarding their argumentation teaching involving two social scientific issue (SSI) scenarios. The results showed that the experienced teacher had more varied and organised MSK for teaching argumentation than the novice teacher. Meanwhile, the novice teacher indicated a belief that the learning of argumentation should occur in a more student-centred manner, rather than relying on a traditional lecture-based environment. Consequently, she spent a considerable amount of time engaging students with their peers' ideas through discussion and collaboration. On the other hand, the experienced teacher noticed that most of students had the ability to generate arguments, but that few knew how to argue based on evidence. Therefore, she helped students to collect data from various resources and suggested that they construct their own knowledge framework in order to improve students' ability to incorporate their understanding of scientific knowledge into scientific argumentation.